Efforts to Improve Islamic Education Learning Outcomes Through Storytelling Methods and Visual Media at SD Negeri Lamteubee - Yusnidar; Nurainun (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the learning outcomes of Islamic Religious Education on the material about the angels of Allah through the storytelling method and visual media. This study is a classroom action research that uses four steps, namely planning, action, observation, and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests were used to measure student learning outcomes before and after the application of the storytelling method and visual media, while observations were used to analyze the learning activities of teachers and students during the learning process. The data analysis techniques used in this study were qualitative and quantitative descriptive analysis. Qualitative data were obtained from observation results and analyzed using thematic analysis methods, while quantitative data were obtained from test results and analyzed by calculating the increase in students' average scores before and after the action. The results showed that the use of storytelling methods and visual media can improve student learning outcomes in Islamic education learning, increase active participation in learning, and help students understand and remember material about the angels of Allah more easily. Thus, the use of storytelling methods and visual media can be used as an effective learning strategy in improving students' understanding and learning outcomes in Islamic Religious Education subjects, especially in material about the angels of Allah.